Association of vitamin D deficiency and subclinical diabetic peripheral neuropathy in type 2 diabetes patients - Sun, Xiaoyang; Yang, Xinyu; Zhu, Xiaopeng; Ma, Yu; Li, Xu; Zhang, Yuying; Liu, Qiling; Fan, Chenmin; Zhang, Miao; Xu, Binger; Xu, Yanlan; Gao, Xin; et al. (Frontiers in Endocrinology, 2024)
Background Diabetic peripheral neuropathy (DPN) contributes to disability and imposes heavy burdens, while subclinical DPN is lack of attention so far. We aimed to investigate the relationship between vitamin D and distinct subtypes of subclinical DPN in type 2 diabetes (T2DM) patients. Methods This cross-sectional study included 3629 T2DM inpatients who undertook nerve conduction study to detect subclinical DPN in Zhongshan Hospital between March 2012 and December 2019. Vitamin D deficiency was defined as serum 25-hydroxyvitamin D (25(OH)D) level < 50 nmol/L. Results 1620 (44.6%) patients had subclinical DPN and they were further divided into subgroups: distal symmetric polyneuropathy (DSPN) (n=685), mononeuropathy (n=679) and radiculopathy (n=256). Compared with non-DPN, DPN group had significantly lower level of 25(OH)D (P < 0.05). In DPN subtypes, only DSPN patients had significantly lower levels of 25(OH)D (36.18 ± 19.47 vs. 41.03 ± 18.47 nmol/L, P < 0.001) and higher proportion of vitamin D deficiency (78.54% vs. 72.18%, P < 0.001) than non-DPN. Vitamin D deficiency was associated with the increased prevalence of subclinical DPN [odds ratio (OR) 1.276, 95% confidence interval (CI) 1.086-1.501, P = 0.003] and DSPN [OR 1. 646, 95% CI 1.31-2.078, P < 0.001], independent of sex, age, weight, blood pressure, glycosylated hemoglobin, T2DM duration, calcium, phosphorus, parathyroid hormone, lipids and renal function. The association between vitamin D deficiency and mononeuropathy or radiculopathy was not statistically significant. A negative linear association was observed between 25(OH)D and subclinical DSPN. Vitamin D deficiency maintained its significant association with subclinical DSPN in all age groups. Conclusions Vitamin D deficiency was independently associated with subclinical DSPN, rather than other DPN subtypes.